2016
DOI: 10.1111/cdev.12542
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of Cultural Learning

Abstract: Developmental research has the potential to address some of the critical gaps in our scientific understanding of the role played by cultural learning in ontogenetic outcomes. The goal of this special section was to gather together leading examples of research on cultural learning across a variety of social contexts and caregiving settings. Although the field of developmental psychology continues to struggle with the persistent problem of oversampling U.S. and Western European populations, we argue that the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 72 publications
0
59
0
2
Order By: Relevance
“…Previous research has shown that whereas some cultural differences in social behaviour emerge early in development (Legare & Harris, 2016;Nielsen & Haun, 2016;Over & Uskul, 2016), certain aspects of intergroup cognition appear to show cultural invariance (Dunham, Baron, & Banaji, 2006;Dunham, Srinivasan, Dotsch, & Barner, 2014). Understanding the nature and extent of cultural variation must be a priority for developmental research, especially research centering on the construction and transmission of social information, such as that relating to groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that whereas some cultural differences in social behaviour emerge early in development (Legare & Harris, 2016;Nielsen & Haun, 2016;Over & Uskul, 2016), certain aspects of intergroup cognition appear to show cultural invariance (Dunham, Baron, & Banaji, 2006;Dunham, Srinivasan, Dotsch, & Barner, 2014). Understanding the nature and extent of cultural variation must be a priority for developmental research, especially research centering on the construction and transmission of social information, such as that relating to groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural variability is one of our species' most distinctive features, and a causal account of human culture must explain its diversity. The psychological adaptations supporting cumulative cultural transmission are hypothesized to be universal features of human psychology, but they must be sufficiently flexible to support the acquisition of highly variable skill sets and behavioral repertoires (38).…”
mentioning
confidence: 99%
“…Alongside this portrayal of the child as a young scientist who steadily builds up a coherent and objective conception of the natural world, recent developmental research has paid increasing attention to the ways in which infants and young children can also be viewed as anthropologists. They are cultural learners, receptive to information from other people, including caregivers, adult members of their group, and peers, especially regarding the distinctive languages, beliefs, and practices of the culture that they live in (5)(6)(7)(8).…”
mentioning
confidence: 99%